2014
DOI: 10.1002/jib.179
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genetic variability of barley accessions (Hordeum vulgareL.) irrigated in the savannas based on malting quality traits

Abstract: The purpose of the study was to characterize and quantify the genetic variability of 30 elite barley malt accessions irrigated in the savannas, using traits related to the industrial quality to verify if they could be used in improvement programmes in the selection of better malt quality genotypes. The following analytical determinations were carried out: total protein content (%), extract yield M.F. i.a. (%), Hartong index VZ (45°C), viscosity 8.6°P (mPa s), boiled wort colour (EBC), soluble nitrogen content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…According to the mean of these analyses, there were differences between the genotype of at least one standard deviation for the industrial quality variables, with the exception of total protein, viscosity and wort colour. Similar results were found under irrigated conditions in the Brazilian savanna, by Evans et al and Verma and Sarkar , indicating the existence of probable genotypic variability among the 38 genotypes of barley that were evaluated.…”
Section: Resultssupporting
confidence: 86%
“…According to the mean of these analyses, there were differences between the genotype of at least one standard deviation for the industrial quality variables, with the exception of total protein, viscosity and wort colour. Similar results were found under irrigated conditions in the Brazilian savanna, by Evans et al and Verma and Sarkar , indicating the existence of probable genotypic variability among the 38 genotypes of barley that were evaluated.…”
Section: Resultssupporting
confidence: 86%
“…In the evaluated set of genotypes, a strong negative correlation was detected between the Kolbach index and the content of β-glucans in wort (r = -0.72). A similar correlation was also found by Jin et al (2011) and Amabile et al (2014).…”
Section: Table 8 Matrix Of Correlation Between the Studied Traits In supporting
confidence: 87%
“…The values ranged from 27.3 to 62.9%. Amabile et al (2014) reported the range of values of the Kolbach index in a set of 30 malting two-row and six-row barley mainly from the area of South America in the range of 38.7-64.8%. In the observed set, the group from South America and Australia (35.9%) together with the group from the Middle East and Africa (36.6%) differed statistically significantly in this parameter from the other groups (Table 7).…”
Section: Level Of Proteolytic Modificationmentioning
confidence: 99%
“…Barley is one of the best cereals for cultivation in dry and semi-dry areas. It is the world's fourth most important cereal in terms of production, (after wheat, rice, and maize) and is the second most important (after wheat) in the Middle East and North Africa (Amabile et al, 2014). The effective management of barley production is complicated by a number of contingency factors, which makes it almost unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to study the divergence and genetic relationships among the barley accessions since the characterisation of genetic variability helps to identify better genotypes which could be used in hybridisations as parents and improves quality of agricultural products (Amabile et al, 2014). The use of factor analysis in this context can help to reduce a large set of traits to a smaller but meaningful set of traits, thereby allowing researchers and practitioner to identify trait that contributes to maximum variability since genetic improvements largely depends on the magnitude of genetic variation (Parvathaneni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%